The return of vulgar economics: A rejoinder to Colander, Holt and Rosser - Matias Vernengo (The University of Utah, Department of Economics, 2011)
This paper provides a rejoinder to Colander, Holt and Rosser (2010) strategy to win friends and influence mainstream economics. It is suggested that their strategy is counter-productive, and while it might gain them friends, it will not lead to increased influence of heterodox ideas within what they term the cutting edge of the profession. It is argued that their failure to understand the nature of heterodoxy, and the reason for the eclecticism of the mainstream, associated to the rise of vulgar economics, undermines their arguments.
Keywords: B41; B59; 330; Methodology; Heterodox Economics